2020
DOI: 10.1016/j.jclepro.2019.118568
|View full text |Cite
|
Sign up to set email alerts
|

Design and properties of 100% waste-based ternary alkali-activated mortars: Blast furnace slag, olive-stone biomass ash and rice husk ash

Abstract: Alkali-activated cements (AACs) technology is being widely investigated as a replacement for ordinary Portland cement (OPC) for environmental benefits. Blast furnace slag (BFS) is one of the most well known precursors used in AACs, having comparable properties to those of traditional OPC-based materials. AACs require alkali solutions, which are commonly based on a combination of sodium or potassium hydroxides with sodium or potassium silicates in high concentration. These alkali solutions represent the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 35 publications
0
18
0
3
Order By: Relevance
“…Among the main waste considered to be a source of silica are ashes from agro-industrial waste, e.g., rice husk ashes, sugar cane straw ashes, or biomass ashes. All these ashes have been studied by different researchers, and it has been observed that they contain important chemical elements from the point of view of cementing materials such as silicon, aluminium, and sodium/potassium [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the main waste considered to be a source of silica are ashes from agro-industrial waste, e.g., rice husk ashes, sugar cane straw ashes, or biomass ashes. All these ashes have been studied by different researchers, and it has been observed that they contain important chemical elements from the point of view of cementing materials such as silicon, aluminium, and sodium/potassium [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-activated mortar and concrete materials have shown a commendable mechanical performance and thus such production techniques have been considered as alternative processes for the production of construction materials despite the yet low acceptance by the industry. Aside fly ash (FA) and ground granulated blast furnace slag (GGBS) have been extensively studied in the production of AAM, and other potential precursors rich in amorphous Al 2 O 3 and SiO 2 include: Agricultural wastes and aquaculture farming ashes : rise husk ash [ 1 , 2 ], palm oil fuel ash [ 3 , 4 , 5 , 6 ], corn cob ash [ 7 , 8 ], sugarcane bagasse ash [ 9 ], straw ash [ 7 , 10 ], forest biomass bottom ash [ 11 ], wood ashes [ 12 , 13 ], other agriculture-farming wastes (e.g., alfalfa steam ash, cotton gin ash, com stalk ash and switch grass ash [ 7 , 14 , 15 ]), and shell wastes [ 16 , 17 ]; Industrial waste ashes : FA [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], coal bottom ash [ 28 ], industrials slags [ 3 , 20 , 29 , 30 , 31 , 32 , 33 , 34 ], silica fume [ 35 , …”
Section: Introductionmentioning
confidence: 99%
“…Industrial waste ashes : FA [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], coal bottom ash [ 28 ], industrials slags [ 3 , 20 , 29 , 30 , 31 , 32 , 33 , 34 ], silica fume [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], artificial pozzolans (calcined clays [ 34 , 43 , 44 , 45 ], ceramic residues [ 46 , 47 ], sedimentary rocks containing clay minerals and burned bauxites [ 48 , 49 , 50 ]), natural pozzolans (volcanic tuffs/zeolites [ 51 , 52 ], siliceous such as opal and diatomaceous earth [ 53 , 54 , 55 , 56 , 57 ], and volcanic glasses such as volcanic ashes [ 58 , 59 , 60 , 61 ,…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline activators used are strong alkaline solutions (NaOH, Na 2 CO 3 or hydrated alkali silicates). These alkaline materials can lead to a reduction in CO 2 emissions of between 55%-75% compared to the manufacture of Portland cement [8]. Geopolymers are characterized by having low hydration heats, high mechanical performance, and good durability against different aggressive agents (acidic media [9], sulfate attack [10], fire [11], etc.…”
Section: Introductionmentioning
confidence: 99%